Beijing process and follow-up : Bangladesh perspective - Huq, Jahanara; Sālāhauddina, Khāledā.; Hāmidā Ākhatāra Begama, 1941-; Women for Women (Organization : Bangladesh); Workshop on Beijing Process and its Follow-up in Bangladesh (1996? : Dhaka, Bangladesh?) (Dhaka : Women for Women, 1997)
On gender equality and justics; papers relating to the Workshop on Beijing Process and its Follow-up in Bangladesh.
Includes bibliographical references.
Keywords: Women -- Bangladesh -- Social conditions; Women's rights -- Bangladesh; Women -- Government policy -- Bangladesh